Simultaneous study on flame propagation behavior and pollutant formation characteristics of ammonia premixed combustion ignited by a methanol ignition chamber - Chunyang Xie; Mingfei Lu; Yangyang Zhang; Zhenyu Sun; Pengbo Dong; Wuqiang Long; Peng Wang; Yang Wang; Ge Xiao; Hua Tian (Fuel, 2026)

Experimental study on evaporation characteristics of liquids in a bottom-heated cylindrical pool under low-pressure environment - Xu-Ge Wang; Chuan-Long Ge; Chun-Mei Wu; You-Rong Li (Desalination, 2026)

A novel drilling-jetting integrated technology with curved channel: Relationship between energy loss and jet diffusion, and its field application - Xiangjie Liu; Zhaolong Ge; Zhe Zhou; Jie Long; Yiyu Lu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Bipyridine-based covalent organic framework for trace-level nanofluidic detection of chlorobenzoquinone - Xu-Qin Ran; Xin-Ge Cai; Xiao-Jiao Ren; Xiu-Ping Yan; Hai-Long Qian (Chemical Engineering Journal, 2026)

Carbon sources regulate extracellular polymeric substance molecular architecture to alter antibiotic removal pathways and lipid accumulation in microalgae - Hongmei Ge; Fangyuan Liu; Zhuoyu Bu; Shulian Wang; Long Cheng; Kai Cheng; Yibo Zhang (Journal of Environmental Chemical Engineering, 2026)

Wind and white: the dual controls of cold waves on surface urban heat islands in China - Xiang Li; Wenfeng Zhan; Huilin Du; Shasha Wang; Chunli Wang; Yingying Ji; Chenguang Wang; Zihan Liu; Jiufeng Li; Long Li; Yihan Gao; Shuang Ge (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Landfill aging enhances chlorinated organophosphate adsorption on microplastics: Mechanistic insights and elevated risks for biodegradable polymers - Dongsheng Shen; Yujie Xuan; Beixiao Ge; Yaqing Liu; Yuyang Long; Jiali Shentu; Li Lu; Min Zhu (Journal of Hazardous Materials, 2026)

Investigation of changes in microbial communities and metabolites for the nutrient re-utilization of fermented agricultural wastes in watermelon - Tong-Lu Wei; Yan-Ge Li; Mao-Song Pei; Hai-Nan Liu; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Biomass and Bioenergy, 2026)

Identification and Heterologous Spatial Distribution of Eleven Novel Brominated Flame Retardants in Soil from Three Petrochemical Industrial Parks and a Flame Retardant Manufacturing Base - Helong Ren; Meibao Li; Chaoyang Long; Xiang Ge; Zhaofa Huang; Yingxin Yu (Water, Air, & Soil Pollution, 2026)

A synergistic strategy combining passive insulation and active discharge for mitigating thermal runaway propagation in lithium-ion batteries - Peng Liu; Xingyu Long; Tao Cao; Jiayi Ge; Wenhao Zhu; Gang Wu; Lin Hu (Process Safety and Environmental Protection, 2026)

Structural characterization and biological activities of specialized metabolites from mangrove-derived fungi Aspergillus sp. - Jiajia Liu; Yue Zeng; Xinxu Ge; Yang Long (Phytochemistry, 2026)

Corrigendum to“Functional characterization of odorant binding proteins involved in detection of host plant volatiles from the moringa pest Noorda blitealis” [Insect Biochem. Mol. Biol. 192 (2026) 104578] - Yunkang Ge; Zubing Zhang; Ping Gao; Wenkai Liang; Jiming Long; Jiaying Zhu (Insect Biochemistry and Molecular Biology, 2026)

The effects of the “ten-year fishing ban” on phytoplankton in eutrophic shallow lakes: A case study in Lake Gehu, China - You Ge; Dongpo Xu; Shulun Jiang; Long Ren; Yuxin Ye; Zhiyu Feng; Xue Xue (Journal of Environmental Management, 2026)

Functional characterization of odorant binding proteins involved in detection of host plant volatiles from the moringa pest Noorda blitealis - Yunkang Ge; Zubing Zhang; Ping Gao; Wenkai Liang; Jiming Long; Jiaying Zhu (Insect Biochemistry and Molecular Biology, 2026)

A theoretical model for local buckling of FRP-confined CFST columns - Yue-Ling Long; Xiang-Hua Yue; Sheng Ge; Leroy Gardner; M. Ahmer Wadee (Engineering Structures, 2026)

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

Monitoring algal blooms in eutrophic inland lakes using OLCI: Overcoming cloud and sun-glint effects on low-quality imagery - Bingqian Han; Shaojing Wang; Long Fei; Kaishan Song; Ge Liu; Yue Ma; Shidi Shao; Yang Li; Yujin Zhou; Jipeng Zhang (Journal of Hazardous Materials, 2026)

Unveiling the modulatory role of microplastics in the release of chlorinated organophosphorus flame retardants from landfill soils - Li Lu; Yujie Xuan; Xuke Wang; Beixiao Ge; Yuyang Long; Jiali Shentu; Dongsheng Shen; Min Zhu (Environmental Research, 2026)

Resilience of Dehalococcoides enables complete reductive dechlorination of trichloroethene to ethene under high PFOS stress - Fang Zhang; Runlei Ge; Chongwen Shi; Tao Long; Kun Yang; Guanghe Li; Lifeng Cao (ENGINEERING Environment, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Precambrian evolution of China: Preface - Xiaoping Long; Rongfeng Ge; Wei Wang; Wei Wang (Precambrian Research, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Unraveling the synergy of wheat-based probiotic- fermented modified dietary Fibers, resistant starch, and gluten in constructing high-quality, low Glycemic index noodles - Ai-Mei Liao; Xiao-ge Liu; Qiao-Qiao Lai; Jia-qi Wang; Kiran Thakur; Long Pan; Yin-Chen Hou; Na Liu; Xian-ming Liu; Zhao-Jun Wei (Food Chemistry, 2026)

Mechanistic insights into magnetite-enhanced Indoleacetic acid production by a mixed culture - Yun-Xin Ge; Wei Gao; Zi-Han Fan; Yun Niu; Long-Tao Fang; Xi-Zhen Zou; Wei Zhang (Journal of Water Process Engineering, 2026)

Visualization study on combustion characteristics of direct-injection methanol ignited by micro-injection diesel in a hydrogen-rich syngas atmosphere - Yuanyou Tang; Wuqiang Long; Zhizhuo Dai; Zechuan Cui; Yang Wang; Ge Xiao; Pengbo Dong; Hua Tian (Fuel, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Short and long-term impact assessment of urban low-carbon pilot policies on household decarbonization - Jie Xue; Tingting Liu; Feng Long; Chazhong Ge; Zhixiong Weng (Environmental Impact Assessment Review, 2026)

Corrigendum to “Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea” [Lithos 512–513(2025) 108151] - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2026)

Urban–rural gradients in cooling efficiency trends of tree covers across global cities - Chunli Wang; Kaiyuan Li; Wenfeng Zhan; Long Li; Chenguang Wang; Shasha Wang; Sida Jiang; Shuang Ge; Zihan Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Enhancing the functional properties of egg yolk through post-treatments following short-term fermentation for application in powdered oils - Junlin Ge; Qiuyu Ye; Daping Long; Jiajing Liu; Yuting Ye; Jiawen Pei; Xuebo Liu; Xiang Duan (Food Research International, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Zn2+-DTPMPA chelated cellulose nanocrystal hybrid: synergistic flame-retardant, antibacterial and mechanical reinforcement mechanisms for PA66 composites - Gang Long; Xue Ma; HouYong Yu; Meijin Jin; Xuefei Chen; Xiaohua Wang; Zengwen Yao; Dengteng Ge; Cheng Zeng; Shengjian Wang; Haojie Zang; Yi Jiang (Carbohydrate Polymers, 2026)

Distinct roles of nitrogen and phosphorus availability in preventing soil organic carbon loss in alfalfa-converted cropland - Xu-Long Zhang; Ge Li; Xiao-Peng Shi; Yang-Yang Zhao; Hai-Long Ma; Wen-Feng Cong; Fusuo Zhang; Feng-Min Li (Agriculture, Ecosystems & Environment, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Uncovering the sensing power of shared bikes for urban feature monitoring - Wen Ji; Ke Han; Qi Hao; Qian Ge; Ying Long (Journal of Transport Geography, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

Trophic attenuation and transmission of antibiotic resistance in the aquatic food webs - Xue Xue; Shulun Jiang; You Ge; Yongjin Chen; Dongfa Gao; Long Ren; Zhen Kuang (Journal of Hazardous Materials, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Asymmetric CALF-20/PIM-1 MMMs with anisotropic properties for efficient carbon capture - Yuchao Ma; Wei Zhao; Dacheng Zhang; Kaihua Li; Qian Zhang; Ge Wang; Zhanfeng Zhao; Long Jiao; Leixin Yang; Ningning Gao; Bowen Cheng (Chemical Engineering Journal, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Metabolic syndrome and risk of dementia and cognitive decline: a systematic review and meta-analysis of prospective cohort studies from 6,753,197 participants - Qi Wang; Luyi Zhang; Ruiqi Xu; Kexin Meng; Lutong Pan; Xiaoyu Zhang; Long Ge; Dongshan Zhu (GeroScience, 2025)

Microbial modulation of soil pH: A self-benefiting mechanism exemplified by Bacillus - Jichen Wang; Min Qiu; Zhaoyang Shen; Long Chen; Yuan Ge (Soil Biology and Biochemistry, 2025)

Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2025)

From Early Toxicity to Grain Accumulation: Warming Effects on Cadmium Uptake and Translocation in Wheat (Triticum aestivum L.) - Liqiang Ge; Long Cang; Ruihan Chen (Water, Air, & Soil Pollution, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Prediction of next-day 1-km canopy urban heat island by integrating a multi-block convolutional neural network with satellite- and ground-based observations - Shuang Ge; Wenfeng Zhan; Jiufeng Li; Long Li; Pan Dong; Xiang Li; Chenguang Wang; Chunli Wang; Yihan Gao (Sustainable Cities and Society, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Visualization study on the effects of water addition on microscopic and macroscopic spray characteristics of methanol with high-pressure direct injection - Qianming Wang; Wuqiang Long; Wei Sang; Guangjie Jin; Zechuan Cui; Ge Xiao; Hua Tian; Jiangping Tian; Yang Wang (Fuel, 2025)

Phosphorus doped self-grown multiphase molybdate compounds micrometer arrays for efficient HER and OER - Kun Zhang; Yunxia Liang; Shuangqian Liu; Long Wang; Guangtian Ji; Chengwei Yang; Jueming Yang; Jinli Zhang; Guixian Ge (Fuel, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Recent advances of fluorescent carbon dots for biological imaging and biosensing - Jing Bian; Zheng Wang; Jinnian Ge; Wanqing Gong; Kaisheng Nan; Zefang Liu; Jinlu Guo; Qinfu Zhao; Xiaofan Wang; Long Wan (Chemical Engineering Journal, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Symmetrical response of plant diversity but asymmetrical response of biomass production to rainfall reduction and addition in global grasslands - Ge Li; Xu-Long Zhang; Josep Peñuelas; Jordi Sardans; Ying Zhao; Yan Yu; Jian-Sheng Ye (Plant and Soil, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Weathering and recycling controls on rare earth element behavior: A comparative study on granitic, basaltic and aeolian red soil crusts - Long Han; Bin Lü; Chaoqiang Li; Jiao Yang; Wenjing Ge; Jianlei Gao; Xingxing Wang; Yan Zheng (Geochimica et Cosmochimica Acta, 2025)

Effects of jets interaction and injection strategy on the combustion characteristics in TJI-HPDI methanol engine - Peng Wang; Wuqiang Long; Wentao Zhao; Mingfei Lu; Pengbo Dong; Hua Tian; JingChen Cui; Ge Xiao; Yang Wang; Jianlin Cao (Fuel, 2025)

The synergistic impact of cadmium and the wheat rhizosphere on the soil bacterial community in alkaline cropland in Northern China - Wenjing Ge; Fukun Gao; Jianlei Gao; Junxiang Ding; Long Han; Jing Wang; Tengyun Zhang; Hongli Li; Yixin Yan (Journal of Soils and Sediments, 2025)

Development of dynamic topology optimization method for offshore jacket platforms - Yu-Tao Guo; Kang Ge; Chen Wang; Xiao-Long Zhao; Bin-Bin Li (Ocean Engineering, 2025)

3D printing of self-powered triboelectric intelligent system with enhanced output performance for material identification via machine learning - Bingyu Huang; Kailong Xu; Xiaofei Zhang; Yongcheng Zhang; Yun-Ze Long; Shuzhi Sam Ge; Xiangxia Wei (Chemical Engineering Journal, 2025)

Visible light can also efficiently activate chlorine dioxide for the abatement of micropollutants - Bin Zhang; Zhiyun Long; Ge Zeng; Wenjun Zhang; Peng Su; Xiangyang Hou; Qixiao Lv; Wenqi Li; Jin Jiang; Zihao Wu; Tao Yang (Chemical Engineering Journal, 2025)

Branch segmentation and phenotype extraction of apple trees based on improved Laplace algorithm - Long Li; Wei Fu; Bin Zhang; Yuqi Yang; Yun Ge; Congju Shen (Computers and Electronics in Agriculture, 2025)

Height and terrain correction of UAV radioactive measurements based on DEM data - Zhipeng Deng; Liangquan Ge; Long Wen; Shengliang Guo; Chuanfeng Tang; Peng Yu; Zekuan Chen (Journal of Environmental Radioactivity, 2025)

Experimental and simulation study on the performance of corrugated plate enhanced solar chimney power plant combined with distillation system - Lu Zuo; Chenkai Xiao; Ziyang Yan; Zinan Guo; Long Huang; Yunting Ge (Desalination, 2025)

Stratified distribution of recycled components in the mantle of the South China Sea unveiled through magnesium isotopes - Zhen-Min Ge; Xiao-Long Huang; Fan Yang; Yang Yu; Guan-Hong Zhu; Le Zhang; Yu-Xin Cai; Guo-Hong Sun (Chemical Geology, 2025)

Late Miocene paleo-seismic events and tectonic responses of the western Qinling Mountains recorded in aeolian deposits - Long Chen; Zhengtang Guo; Xin Zhou; Junyi Ge; Chaoqin Chen; Zhilin He (Science China Earth Sciences, 2025)

Non-invasive Modulation of Deep Brain Nuclei by Temporal Interference Stimulation - Long Li; Hao Bai; Linyan Wu; Liang Zheng; Liang Huang; Yang Li; Wenlong Zhang; Jue Wang; Shunnan Ge; Yan Qu; Tian Liu (Neuroscience Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Bacterial assemblies in acidic dryland vs. paddy soils across depth profiles in southern China's red soil region - Xin Li; Yun Ge; Fangjing Hu; Yongxiu Qi; Lingzhi Li; Xu Chen; Xi-En Long (Pedobiologia, 2025)

Study on the mechanism of pseudo-interpenetrating network enhancing recyclable VES-CO2 foam system and the key performance as fracturing fluid - Nanxin Zheng; Jingyi Zhu; Zhaozhong Yang; Chao Song; Xiaogang Li; Yufeng Long; Liangping Yi; Jianlin Lai; Jingnan Ge (Fuel, 2025)

Identification and spatial distribution of organophosphorus flame retardants in surface soils from typical petrochemical industry and flame retardant production parks in China - Zhiyong Fan; Chaoyang Long; Xiang Ge; Zhaofa Huang; Helong Ren; Yingxin Yu; Taicheng An (Environmental Pollution, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

Myeloid-derived suppressor cells alleviate adverse ventricular remodeling after acute myocardial infarction - Yan-Ge Wang; Ding-Hang Wang; Wen-Hui Wei; Xin Xiong; Jing-Jing Wu; Zhan-Ying Han; Long-Xian Cheng (Molecular and Cellular Biochemistry, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Antitussive drug dextromethorphan induces developmental impairment in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Zhi-Jie Lu; Jin-Ge Zhang; Li-Xin Hu; Zheng Huang; Si-Ying Li; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Crystal face-induced and defect-optimized V2O5 thin films: Boosting multicolor dual-band electrochromism - Lingjie Hu; Liuying Wang; Gu Liu; KeJun Xu; Chaoqun Ge; Long Wang; Bin Wang; Tonghao Liu (Chemical Engineering Journal, 2025)

A high-precision saltwater ice thickness and salinity detection method based on capacitive coupled planar microwave resonator - Han Shi; Mengjie Song; Junfeng Ge; Long Zhang; Xuan Zhang (Cold Regions Science and Technology, 2025)

Evaluation of enzyme activity predictions for variants of unknown significance in Arylsulfatase A - Shantanu Jain; Marena Trinidad; Thanh Binh Nguyen; Kaiya Jones; Santiago Diaz Neto; Fang Ge; Ailin Glagovsky; Cameron Jones; Giankaleb Moran; Boqi Wang; Kobra Rahimi; Sümeyra Zeynep Çalıcı; et al. (Human Genetics, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Study on the effect of domesticated Escherichia coli on desulphurisation and spontaneous combustion oxidation characteristics of coals with varying sulphur contents - Xin Yi; Min Zhang; Jun Deng; Yang Xiao; Xinfu Shi; Long Ge (Fuel, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Enhanced visual detection of litchi fruit in complex natural environments based on unmanned aerial vehicle (UAV) remote sensing - Changjiang Liang; Juntao Liang; Weiguang Yang; Weiyi Ge; Jing Zhao; Zhaorong Li; Shudai Bai; Jiawen Fan; Yubin Lan; Yongbing Long (Precision Agriculture, 2025)

Optimized acid leaching synthesis and steam regeneration of the steel slag-derived calcium-based sorbent for enhanced CO2 capture - Nai Rong; Xiuliang Shi; Shanshan Wang; Long Han; Kaiwei Liu; Lichao Ge; Yuhan Wang; Geng Wang (Journal of Cleaner Production, 2025)

Parametric study on the methanol/diesel JCCI mode with dual-direct injection system in a light-duty engine - Bo Li; Wei Tan; Yunpeng Wei; Liyun Fan; Yang Wang; Xianyin Leng; Ge Xiao; Wuqiang Long (Fuel, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Constructing Pb-O bonds to trigger efficient cross-scale charge transfer for high-performance electromagnetic wave absorption and multicolor conversion - Jie Huang; Lingjie Hu; Liuying Wang; Weichao Wang; Chaoqun Ge; Long Wang; Mengzhou Chen; Renbing Wu; Gu Liu; Bin Wang (Chemical Engineering Journal, 2025)

Intelligent cooperative control for flexible landing on small celestial bodies - Pingyuan Cui; Dongyue Zhao; Zelong Chen; Dantong Ge; Jiateng Long (Advances in Space Research, 2025)

Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Shuyan Wang; Ying Xiong; Hushun Zhang; Dade Song; Yanping Wang; Hui Ge; Chengbin Zhang; Long Liang; Xiaming Zhong (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus . Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year -1 , and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year -1 , 0.79 year -1 , and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

“Gear-like” process between asymmetric dipole eddies from satellite altimetry - Shuang Long; Fenglin Tian; Ying Ma; Chuanchuan Cao; Ge Chen (Remote Sensing of Environment, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Research on operation characteristics of wind supercharged solar chimney dust haze removal street light - Lu Zuo; Zinan Guo; Tian Zhou; Chenkai Xiao; Long Huang; Yunting Ge (Process Safety and Environmental Protection, 2024)

Enhancing energy yield and reducing environmental impact through co-hydrothermal carbonization of undehydrated sewage sludge and fungus bran - Shuai Guo; Jiyou Mu; Long Gao; Liya Ge; Grzegorz Lisak (Journal of Environmental Chemical Engineering, 2024)

Cost-effective degradation of ultra-high concentration polyvinyl alcohol through peroxymonosulfate based oxidation using nano spinel CoFe2O4 deposited acidified diatomite as the catalyst - Shuang Zhai; Yanyan Li; Xiaoyun Long; Haisang Liu; Mingqiao Ge; Qilong Sun; Yiwei Chen (Journal of Environmental Chemical Engineering, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Nonlinearly coupled electro-osmotic flow in variable charge soils - Xiaojuan Yang; Ge Shi; Chao Wu; Ye Yuan; Honglei Sun; Long Cang (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

An experimental study on the defrosting performances of an ASHP having a novel dual-fan outdoor coil under different levels of frosting evenness along airflow direction - Xiaoxia Bai; Zhong Ge; Shiming Deng; Minglu Qu; Xuejing Sang; Long Zhang (Energy and Buildings, 2024)

Organofluorinated Ag/2D diamond nanocomposites achieve simultaneously ultra-low friction and wear in self-lubricating epoxy - Qingzhao Cai; Chengcheng Jiao; Junhao Wu; Shanqin Ge; Wei Li; Long Chen; Genxiang Gong; Jiamin Yu; Yaokang lv; Jinhong Yu; Kazuhito Nishimura; Nan Jiang; et al. (Chemical Engineering Journal, 2024)

The accumulation of cadmium and lead in wheat grains is primarily determined by the soil-reducible cadmium level during wheat tillering - Jing Wang; Tengyun Zhang; Jianlei Gao; Bei Li; Long Han; Wenjing Ge; Zongyao Wang (Chemosphere, 2024)

Geochronology and Sr-Nd-Pb-Hf-O isotopes of Neoproterozoic orthogneisses in the Jiamusi Block, NE China: Implications for tectonic origin and secular crustal evolution - Xin Ding; Hao Yang; Zheng Ji; Yan-Long Zhang; Hao-Ran Wu; Yu Dong; Guan-Ying Yu; Wen-Chun Ge (Precambrian Research, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Colorimetric aptasensor utilizing MOF-235 with exceptional peroxidase-like activity for the detection of oxytetracycline residues in raw milk - Long Wang; Xia Lu; Yan Zhang; Yuxin Wang; Yi Ding; Mengjia Liu; Shangchen Fu; Wupeng Ge (Food Chemistry, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Photosensitization of riboflavin reduces the susceptibility to gray mold in postharvest kiwifruit - Yuhan Long; Yue Sun; Bei Zhou; Ge Zhu; Xiaolong Chen; Yongjie Qi; Ke Wang (Postharvest Biology and Technology, 2024)

The azole biocide climbazole induces oxidative stress, inflammation, and apoptosis in fish gut - Zhi-Jie Lu; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Xiao-Bing Long; Si-Ying Li; Fang-Zhou Gao; Qian-Qian Zhang; Guang-Guo Ying (Science of The Total Environment, 2024)

Changes in preferential flow caused by root effects in black locust plantations of different stand ages in the semi-arid region of the Loess Plateau - Lu Cai; Fei Wang; Yuanyuan Lin; Qi Long; Yulong Zhao; Jianqiao Han; Wenyan Ge; Hao Chen (Journal of Hydrology, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Over-expansion cycle as clean combustion strategy applied to a marine low-speed dual fuel engine - Jianlin Cao; Yang Wang; Dongsheng Dong; Fuxing Wei; Heng Zhang; Longlong Jiang; Pengbo Dong; Bo Li; Ge Xiao; Wuqiang Long (Journal of Cleaner Production, 2024)

Characterization and prediction modeling of membrane distillation enhanced disc solar still - Lu Zuo; Chenkai Xiao; Ziyang Yan; Long Huang; Zinan Guo; Yunting Ge (Journal of Cleaner Production, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Effects of New Psychoactive Substance Esketamine on Behaviors and Transcription of Genes in Dopamine and GABA Pathways in Zebrafish Larvae - Si-Ying Li; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

An azole fungicide climbazole damages the gut-brain axis in the grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Experimental study on the effects of water addition in methanol on the performance of diesel-methanol diffusion combustion on a high-speed engine - Qianming Wang; Yang Wang; Ge Xiao; Xiaoyu Chen; Jianlin Cao; Yang Wang; Wuqiang Long (Journal of Cleaner Production, 2024)

Shear mechanical properties of the interphase between the S–RM and benched bedrock using the FDM–DEM - Yiliang Tu; Xin'ge Deng; Xingchi Wang; Chengtao Zhou; Lizhou Zhang; Hejun Chai; Xinrong Liu; Qianglong Yao; Hang Long (Computers and Geotechnics, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Contribution of recycled oceanic crust to the extremely light molybdenum isotopic compositions of mid-ocean ridge basalts from the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Jie Li; Fan Yang; Zhen-Min Ge (Chemical Geology, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Metasomatized mantle source of nascent oceanic crust in the Guaymas Basin, Gulf of California - Zhen-Min Ge; Xiao-Long Huang; Wei Xie; Tobias W. Höfig; Fan Yang; Yang Yu; S. Khogenkumar Singh (Chemical Geology, 2024)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Construction of floatable flower-like plasmonic Bi/BiOCl-loaded hollow kapok fiber photocatalyst for efficient degradation of RhB and antibiotics - Yankai Song; Anchun Long; Xianlong Ge; Zongqi Bao; Minfeng Meng; Shaohua Hu; Yingying Gu (Chemosphere, 2023)

Numerical simulation of gas production behavior of class Ⅰ, class Ⅱ and class Ⅲ hydrate reservoirs for different well locations - Kun Ge; Jiaxing Liu; Jiaqi Wang; Zhen Long; Xinyu Zhang; Haoqi Wei; Wei Yu (Journal of Cleaner Production, 2023)

Investigation on jet controlled diffusion combustion (JCDC) mode applied on a marine large-bore two-stroke engine - Jianlin Cao; Dongsheng Dong; Fuxing Wei; Wuqiang Long; Ge Xiao; Longlong Jiang; Bo Li; Yang Wang (Journal of Cleaner Production, 2023)

Development of injectable hyaluronic acid-based hydrogels with antioxidant activity for the treatment of corneal neovascularization - Linyu Long; Zhengwei Ge; Fanjun Zhang; Ruiqi Dong; Li Yang; Zhongping Chen; Shibo Tang; Yunbing Wang (Chemical Engineering Journal, 2023)

Ephedrine and cocaine cause developmental neurotoxicity and abnormal behavior in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Aquatic Toxicology, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Optical experiment study on Ammonia/Methanol mixture combustion performance induced by methanol jet ignition in a constant volume combustion bomb - Fuxing Wei; Mingfei Lu; Wuqiang Long; Dongsheng Dong; Pengbo Dong; Ge Xiao; Jiangping Tian; Hua Tian; Peng Wang (Fuel, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Chemical functionalization of commercial Pt/C electrocatalyst towards formic acid electrooxidation - Zi-Xin Ge; Bo-Qiang Miao; Xin-Long Tian; Bin He; Yu Chen (Chemical Engineering Journal, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Photocatalytic breaking of C-C bonds in lignin models by combining N-doped carbon nitride and persulfate in micellar aqueous medium - Jie Xu; Xin Zhang; Jing Long; Chang Ge (Journal of Environmental Chemical Engineering, 2023)

Unraveling the carbon dot bridges in oxidized carbon nanotubes for efficient microwave absorption - Jie Huang; Liuying Wang; Bin Wang; Gu Liu; Chaoqun Ge; Long Wang; Weichao Wang; Kejun Xu; Mengzhou Chen; Wenhao Wang; Lingjie Hu; Haiqing Chen (Chemical Engineering Journal, 2023)

Climbazole causes cell apoptosis and lipidosis in the liver of grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Identification of watermelon H3K4 and H3K27 genes and their expression profiles during watermelon fruit development - Yang Qiao; Yan-Ge Li; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Molecular Biology Reports, 2023)

Involvement of the heat shock response (HSR) regulatory pathway in cadmium-elicited cerebral damage - Milton Talukder; Shao-Shuai Bi; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Advances in preparation, interaction and stimulus responsiveness of protein-based nanodelivery systems - Qianzhu Lin; Shengju Ge; David Julian McClements; Xiaojing Li; Zhengyu Jin; Aiquan Jiao; Jinpeng Wang; Jie Long; Xueming Xu; Chao Qiu (Critical Reviews in Food Science and Nutrition, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Tectonic nature, subduction, and closure of the Mudanjiang Ocean: Insights from newly discovered oceanic fragments in the Luobei Heilongjiang Complex - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Xin Ding; Zheng Ji; Yan-Long Zhang; Yu Dong; Wen-chun Ge (Lithos, 2023)

Concurrent dominant pathways of multifunctional products formed from nocturnal isoprene oxidation - Haiwei Li; Long Cui; Yu Huang; Yunjiang Zhang; Junfeng Wang; Mindong Chen; Xinlei Ge (Chemosphere, 2023)

Study on refined mathematical model of solar chimney power plant integrated with seawater desalination and the influence of dewing - Lu Zuo; Long Huang; Pengzhan Dai; Yu Chen; Shi Chen; Yunting Ge (Desalination, 2023)

The green halo effect of China’s OFDI: evidence from countries along the Belt and Road - Xiang Cai; Yongzhe Zhao; Xianhua Wu; Dongming Ge; Xingle Long (Environmental Science and Pollution Research, 2023)

Efficient boron-based electrolytes constructed by anionic and interfacial co-regulation for rechargeable magnesium batteries - Juncai Long; Yongkang An; Zhongzhuo Yang; Ge Zhang; Jianyong Zhang; Shuangshuang Tan; Qinyou An (Chemical Engineering Journal, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Visualization study on combustion characteristics of direct-injected hydrous methanol ignited by diesel in a constant volume combustion chamber - Qianming Wang; Fuxing Wei; Pengbo Dong; Ge Xiao; Zechuan Cui; Jiangping Tian; Xiuyong Shi; Wuqiang Long (Fuel, 2023)

Full-scale experimental and numerical study of smoke spread characteristics in a long-closed channel with one lateral opening - Weixin Tong; Fanliang Ge; Long Ding; Jie Ji; Yuanlong Zhou; Yang Zhou; Fan Zhou (Tunnelling and Underground Space Technology, 2023)

Effect of ambient temperature and water content on emulsified heavy fuel oil droplets evaporation: Evaporation enhancement by droplet puffing and micro-explosion - Xiaoyu Chen; Xi Xi; Ge Xiao; Lenan Zhang; Zixin Wang; Wuqiang Long (Fuel, 2023)

Multiple-objective optimization of Jet Controlled Compression Ignition (JCCI) mode with dual-direct injection in a high-speed light-duty engine - Bo Li; Jian Wang; Heng Zhang; Liyun Fan; Xianyin Leng; Wuqiang Long; Ge Xiao (Fuel, 2023)

Relationship of multiple metals mixture and osteoporosis in older Chinese women: An aging and longevity study - Xiuming Feng; Gaohui Zan; Yue Wei; Xiaoting Ge; Haiqing Cai; Tianzhu Long; Lianguang Xie; Lei Tong; Chaoqun Liu; Longman Li; Lulu Huang; Fei Wang; et al. (Environmental Pollution, 2023)

Gold nanoclusters-engineered dual-emitting nanofibrous film for fluorescent discrimination and visual sensing of explosives - Wenxing Gao; Qiang Li; Wencheng Zhong; Xiaomeng Zhou; Yibo Ge; Qi-Long Yan; Li Shang (Chemical Engineering Journal, 2023)

Genetic-based algorithms for cash-in-transit multi depot vehicle routing problems: economic and environmental optimization - Xianlong Ge; Yuanzhi Jin; Long Zhang (Environment, Development and Sustainability, 2023)

A Time-course Transcriptional Kinetics of Genes in Behavior, Cortisol Synthesis and Neurodevelopment in Zebrafish Larvae Exposed to Imidacloprid and Thiamethoxam - Jin-Ge Zhang; Dong-Dong Ma; Si-Ying Li; Xiao-Bing Long; Fang Liu; Zhi-Jie Lu; Wen-Jun Shi (Bulletin of Environmental Contamination and Toxicology, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

Mitochondrial DNA mutation affects the pluripotency of embryonic stem cells with metabolism modulation - Juntao Qi; Qi Long; Yang Yuan; Yanshuang Zhou; Jian Zhang; Zifeng Ruan; Liang Yang; Yi Wu; Ge Xiang; Wei Li; Hao Wu; Shiwei Du; et al. (Genome Instability & Disease, 2022)

Association of soft drink and 100% fruit juice consumption with all-cause mortality, cardiovascular diseases mortality, and cancer mortality: A systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Long Ge; Honghao Lai; Qi Wang; Qi Wang; Qian Zhang; Min Yin; Sheng Li; Jinhui Tian; Kehu Yang; Jiancheng Wang (Critical Reviews in Food Science and Nutrition, 2022)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Cadmium Through Disturbing MTF1-Mediated Metal Response Induced Cerebellar Injury - Shao-Shuai Bi; Milton Talukder; Hai-Tao Jin; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Neurotoxicity Research, 2022)

Identification and validation of suitable reference genes for quantitative real-time PCR studies in Adiantum reniforme var. sinense - Qi Fu; Lin Xiang; Kai-ge Zhao; Long-qing Chen (Journal of Plant Biochemistry and Biotechnology, 2022)

Testing environmental Kuznets curve hypothesis: considering the impact of Sino-US trade on three main industries in China - Long-kang Wu; Tian-tian Feng; Hui Luo; Xiao-lei Gong; Jian-ping Ge (Environmental Science and Pollution Research, 2022)

Zircon and monazite U-Pb ages of the Mashan Complex of the Jiamusi Block of NE China: a link to Gondwana? - Maohui Ge; Zhuang Li; Long Li; Jinjiang Zhang; Kai Liu (International Geology Review, 2022)

Professional chess expertise modulates whole brain functional connectivity pattern homogeneity and couplings - Limei Song; Huadong Yang; Mingdong Yang; Dianmei Liu; Yanming Ge; Jinfeng Long; Peng Dong (Brain Imaging and Behavior, 2022)

GIS-based spatial prediction of landslide using road factors and random forest for Sichuan-Tibet Highway - Cheng-ming Ye; Rui-long Wei; Yong-gang Ge; Yao Li; José Marcato Junior; Jonathan Li (Journal of Mountain Science, 2022)

Ferrostatin-1 Alleviates White Matter Injury Via Decreasing Ferroptosis Following Spinal Cord Injury - Hongfei Ge; Xingsen Xue; Jishu Xian; Linbo Yuan; Long Wang; Yongjie Zou; Jun Zhong; Zhouyang Jiang; Jiantao Shi; Tunan Chen; Hong Su; Hua Feng; et al. (Molecular Neurobiology, 2022)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Characteristics of dissolved organic matter in lakes with different eutrophic levels in southeastern Hubei Province, China - Weixiang Ren; Xiaodong Wu; Xuguang Ge; Guiying Lin; Mengdie Zhou; Zijie Long; Xinhui Yu; Wei Tian (Journal of Oceanology and Limnology, 2021)

Divergent responses in morphology and life history to an Asplanchna kairomone between attached and free-swimming Brachionus dorcas (Rotifera) - Shan Jiang; Yan Bai; Fan Sun; Le-Le Ge; Yi-Long Xi (Hydrobiologia, 2021)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Experimental study of effect of gradation on compaction properties of rockfill materials - Er-Lu Wu; Jun-Gao Zhu; Ge Chen; Long Wang (Bulletin of Engineering Geology and the Environment, 2020)

Establishment of a maize callus regeneration system from haploid shoot tips - Yun Long; Yun Yang; Fei Ge; Guangtang Pan; Yaou Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Evolution of genes and genomes in the genomics era - Song Ge; Ya-Long Guo (Science China Life Sciences, 2020)

Differentiation of human umbilical cord mesenchymal stem cells into Leydig-like cells with defined molecular compounds - Weiping Ji; Yong Chen; Long Wang; Zhangye Xu; Jahanzeb Ahmed; Renshan Ge; Maoping Chu; Xiaoling Guo (Human Cell, 2020)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Hydrochemical characteristics and irrigation suitability of surface water in the Syr Darya River, Kazakhstan - Weiyan Zhang; Long Ma; Jilili Abuduwaili; Yongxiao Ge; Gulnura Issanova; Galymzhan Saparov (Environmental Monitoring and Assessment, 2019)

Development of β-elemene and Cisplatin Co-Loaded Liposomes for Effective Lung Cancer Therapy and Evaluation in Patient-Derived Tumor Xenografts - Mingxiang Cao; Mengmeng Long; Qiuping Chen; Yapeng Lu; Qianqian Luo; Yue Zhao; Ailing Lu; Cunwang Ge; Li Zhu; Zhongping Chen (Pharmaceutical Research, 2019)

Effects of soil environmental factors and UV aging on Cu2+ adsorption on microplastics - Jie Yang; Long Cang; Qian Sun; Ge Dong; Syed Tahir Ata-Ul-Karim; Dongmei Zhou (Environmental Science and Pollution Research, 2019)

Global trends and future prospects of e-waste research: a bibliometric analysis - Ya Gao; Long Ge; Shuzhen Shi; Yue Sun; Ming Liu; Bo Wang; Yi Shang; Jiarui Wu; Jinhui Tian (Environmental Science and Pollution Research, 2019)

Agricultural labor changes and agricultural economic development in China and their implications for rural vitalization - Li Ma; Hualou Long; Yingnan Zhang; Shuangshuang Tu; Dazhuan Ge; Xiaosong Tu (Journal of Geographical Sciences, 2019)

Sensitive and Selective Detection of Antibiotic D-Penicillamine Based on a Dual-Mode Probe of Fluorescent Carbon Dots and Gold Nanoparticles - Hongwei Ge; Kui Zhang; Huan Yu; Ji Yue; Long Yu; Xinfeng Chen; Tianxin Hou; Khalid A. Alamry; Hadi M. Marwani; Suhua Wang (Journal of Fluorescence, 2018)

Soil microalgae modulate grain arsenic accumulation by reducing dimethylarsinic acid and enhancing nutrient uptake in rice (Oryza sativa L.) - Ya Wang; You Qing Li; Kang Lv; Jin Jin Cheng; Xiao Long Chen; Ying Ge; Xiang Yang Yu (Plant and Soil, 2018)

New views and possibilities of antidiabetic drugs in treating and/or preventing mild cognitive impairment and Alzheimer’s Disease - Kai Long Zhong; Fang Chen; Hao Hong; Xuan Ke; Yang Ge Lv; Su Su Tang; Yu Bing Zhu (Metabolic Brain Disease, 2018)

Farmland function evolution in the Huang-Huai-Hai Plain: Processes, patterns and mechanisms - Yingnan Zhang; Hualou Long; Li Ma; Dazhuan Ge; Shuangshuang Tu; Yi Qu (Journal of Geographical Sciences, 2018)

Low genetic differentiation among altitudes in wild Camellia oleifera, a subtropical evergreen hexaploid plant - Xiaomao Huang; Jiaming Chen; Xiaoqiang Yang; Shihua Duan; Chuan Long; Gang Ge; Jun Rong (Tree Genetics & Genomes, 2018)

Molecular characterization and recombination analysis of porcine reproductive and respiratory syndrome virus emerged in southwestern China during 2012–2016 - Long Zhou; Runmin Kang; Gaosheng Ji; Yiming Tian; Mengyun Ge; Bo Xie; Xin Yang; Hongning Wang (Virus Genes, 2018)

Analysis of the coupled relationship between grain yields and agricultural labor changes in China - Dazhuan Ge; Hualou Long; Yingnan Zhang; Shuangshuang Tu (Journal of Geographical Sciences, 2018)

Phylogenetic relationships of ascomycetes and basidiomycetes based on comparative genomics analysis - Xunbiao Liu; Qianqian Zhang; Xinyao Xia; Xiuyuan Liu; Lei Ge; Long Yang (Genes & Genomics, 2017)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Reversible Absorption and Emission Responses of Nile Blue and Azure A Derivatives in Extreme Acidic and Basic Conditions - Xiu-Li Wang; Ru Sun; Wei-Jin Zhu; Xin-Long Sha; Jian-Feng Ge (Journal of Fluorescence, 2017)

Functional effector memory T cells contribute to protection from superinfection with heterologous simian immunodeficiency virus or simian-human immunodeficiency virus isolates in Chinese rhesus macaques - Ming Sun; Huiwen Zheng; Yingpeng Xie; Bingxiang Li; Haiting Long; Ge Guo; Lei Guo; Jingjing Wang; Ruotong Ning; Yue Li; Longding Liu (Archives of Virology, 2017)

Effects of root morphology and leaf transpiration on Cd uptake and translocation in rice under different growth temperature - Liqiang Ge; Long Cang; Jie Yang; Dongmei Zhou (Environmental Science and Pollution Research, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Chain elongation analog of resveratrol as potent cancer chemoprevention agent - Yan-Fei Kang; Hai-Xia Qiao; Long-Zuo Xin; Li-Ping Ge (Journal of Physiology and Biochemistry, 2016)

Genome-wide analysis of shoot growth-associated alternative splicing in moso bamboo - Long Li; Tao Hu; Xueping Li; Shaohua Mu; Zhanchao Cheng; Wei Ge; Jian Gao (Molecular Genetics and Genomics, 2016)

Long-range fine particulate matter from the 2002 Quebec forest fires and daily mortality in Greater Boston and New York City - Ke Zu; Ge Tao; Christopher Long; Julie Goodman; Peter Valberg (Air Quality, Atmosphere & Health, 2016)

Temporal Variability and Potential Diffusion Characteristics of Dust Aerosol Originating from the Aral Sea Basin, Central Asia - Yongxiao Ge; Jilili Abuduwaili; Long Ma; Dongwei Liu (Water, Air, & Soil Pollution, 2016)

Erratum to: Identification and characterization of microRNAs at different flowering developmental stages in moso bamboo (Phyllostachys edulis) by high-throughput sequencing - Jian Gao; Wei Ge; Ying Zhang; Zhanchao Cheng; Long Li; Dan Hou; Chenglin Hou (Molecular Genetics and Genomics, 2015)

Identification and characterization of microRNAs at different flowering developmental stages in moso bamboo (Phyllostachys edulis) by high-throughput sequencing - Jian Gao; Wei Ge; Ying Zhang; Zhanchao Cheng; Long Li; Dan Hou; Chenglin Hou (Molecular Genetics and Genomics, 2015)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Production of sweet orange somaclones tolerant to citrus canker disease by in vitro mutagenesis with EMS - Hongjuan Ge; Yi Li; Hongyan Fu; Guiyou Long; Li Luo; Ronghua Li; Ziniu Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Effects of different warming patterns on the translocations of cadmium and copper in a soil–rice seedling system - Liqiang Ge; Long Cang; Hui Liu; Dongmei Zhou (Environmental Science and Pollution Research, 2015)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Time lag between carbon dioxide influx to and efflux from bare saline-alkali soil detected by the explicit partitioning and reconciling of soil CO2 flux - Xi Chen; Wen-Feng Wang; Ge-Ping Luo; Long-Hui Li; Yan Li (Stochastic Environmental Research and Risk Assessment, 2013)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Bilateral mechanical and thermal hyperalgesia and tactile allodynia after chronic compression of dorsal root ganglion in mice - Rong-Gui Chen; Wei-Wei Kong; Da-Long Ge; Ceng Luo; San-Jue Hu (Neuroscience Bulletin, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b - Zhi-Bang Deng; Nai-Dong Wang; Dao-Jun Xu; An-Wen Yuan; Meng Ge; Wei Luo; Li-Qun Xue; Xing-Long Yu (Veterinary Research Communications, 2011)

Development of twelve polymorphic microsatellite loci in polyploid endangered Omphalogramma vincaeflora Franch. (Primulaceae) - Yuan Huang; Yong Li; Xiao Hu; Xue-Jun Ge; Chang-Qin Zhang; Chun-Lin Long (Conservation Genetics, 2009)

Low genetic diversity and significant population structuring in the relict Amentotaxus argotaenia complex (Taxaceae) based on ISSR fingerprinting - Xue-Jun Ge; Xian-Long Zhou; Zhong-Chao Li; Tsai-Wen Hsu; Barbara A. Schaal; Tzen-Yuh Chiang (Journal of Plant Research, 2005)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)